Lean em uma pequena empresa de fabricação de estruturas metálicas - Bizetti, Alexandre Daniel (Universidade Federal de São Carlos, 2025)
In a heated market context, companies must operate using economically sustainable models, to develop activities/processes that add value to customers, stakeholders, and their employees. Understanding the value flow of their services and products can be the competitive edge in the market in which they operate. Value means waste-free processes. Waste must be eliminated because the customer does not want to pay for it. In 2023, according to the SEBRAE Agency, the creation of small and medium-sized companies was 6.62% higher compared to the previous year, around 859 thousand new businesses. There is a justification for looking at this group since globally, the vast majority of businesses are under the category of small and medium-sized companies. The use of Lean Thinking is one of the most powerful tools available, creating value while eliminating waste. Using Action Research as a research method in the application of lean manufacturing, a small metal structure manufacturing company opened its doors for this work to be developed, a company that had never applied Lean in its production process. Taking important steps in its journey of continuous improvement, which involves process safety, value stream mapping, creation of key performance indicators, use of the 5S methodology, application of Just-in-time, and inventory control, the company studied and developed strategic actions to achieve results such as freeing up 20% of available physical space for storage and reducing lead time by approximately 53%.
Lean in a small metal structure manufacturing company
Keywords: Manufatura enxuta; Pensamento Lean; Mapeamento do fluxo de valor; 5S; Fabricação de estruturas metálicas; Pequenas empresas; Lean manufacturing; Lean thinking; Value stream mapping; PEMBs, Pre Engineered Metal Buildings; Small business; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; 9. Indústria, Inovação e Infraestrutura